2006
DOI: 10.5301/hip.2008.2460
|View full text |Cite
|
Sign up to set email alerts
|

Early outcomes following minimally invasive total hip arthroplasty using a two-incision approach versus a mini-posterior approach

Abstract: We evaluated early clinical results and radiographic findings of MIS THA using 2-incsion approach and mini-posterior approach. A consecutive series of 35 patients (40 hips) with 2-incision THA and a consecutive series of 35 patients (36 hips) with mini-posterior THA performed in the same period were evaluated. The patient groups were not randomised. At the mean follow-up of 20.2 months (range, 12-36 months), the 2-incision group had significantly earlier ambulation, driving ability and return to work. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…Therefore, there were 21 patients with complete preoperative and 2-month postoperative gait analyses and strength testing, and 19 patients with complete preoperative and 1-year postoperative gait analyses and strength testing. The 19 patients included 11 men and eight women with a mean (± SD) age of 65 ± 12 years (range, 40-85 years) and a mean BMI of 29 ± 5 (range, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Eleven patients had the two-incision surgical technique and eight had the mini-posterior technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, there were 21 patients with complete preoperative and 2-month postoperative gait analyses and strength testing, and 19 patients with complete preoperative and 1-year postoperative gait analyses and strength testing. The 19 patients included 11 men and eight women with a mean (± SD) age of 65 ± 12 years (range, 40-85 years) and a mean BMI of 29 ± 5 (range, [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39]. Eleven patients had the two-incision surgical technique and eight had the mini-posterior technique.…”
Section: Methodsmentioning
confidence: 99%
“…Without suitable controls, it is unclear whether the observed recovery in those reports was attributable to the two-incision technique or to some combination of patient selection, patient education, changes in perioperative analgesia protocols, or rapid rehabilitation protocols [12,25,26,28]. Furthermore, there is a growing body of evidence of increased complication rates with the two-incision minimally invasive technique when compared with other methods [1,31,35]. This has persisted even beyond the learning curve of the individual surgeon [9,27].…”
Section: Introductionmentioning
confidence: 97%
“…Most patients undergoing HA are of working age and are able to return to work by 3-7 weeks, and can gradually return to athletic activity after about 3-6 months as long as all post-operative guidelines are followed. 43,[58][59][60][61] A paucity of evidence exists to best determine the association of factors such as patient ethnicity, home environment or support system, specific physical therapy protocols, or the use of manual therapy on outcomes following HA. Without a base of evidence for these variables, the therapist is unable to extrapolate useful clinical information outside of their own personal experiences or sharing of information from others.…”
Section: Discussionmentioning
confidence: 99%
“…According to a review by Kuijer et al, 60 a patient's ability to return to work post-operatively reduces economic burden as well as improves the patient's economic situation. Tanavalee et al 61 found that a two-incision approach versus a mini-posterior allowed for earlier return to work following HA. Any surgical approach with post-operative restrictions is likely to lead to delayed return to work with greater restrictions leading to a longer period out of work.…”
Section: Exercise Physical Activity and Sportmentioning
confidence: 99%
“…Fifty-four papers (43 full text papers 17,27-68 and 11 abstracts [69][70][71][72][73][74][75][76][77][78][79] ) met the inclusion criteria for the review. In addition, relevant data were supplemented by a published registry report (Norwegian Arthroplasty Register) 11 31,32,40,43,46,58,69,75,77 17 comparative studies, [28][29][30][33][34][35][36]42,44,45,48,52,[54][55][56]74,78 and six case series or registry; 11,39,41,[49][50][51] one was used for the comparison of two mini-incision THR with standard THR (one trial) 57 and nine were relevant to the comparison of two mini-incision with single mini-incision THR, including two trials, 72,73 five comparative studies 38,47,53,71,79 and two case…”
Section: Number and Type Of Studies Includedmentioning
confidence: 99%